Spontaneous Spiral Dissection of the Left Anterior Descending Coronary Artery in a Reformed Smoker (Indian Journal of Case Reports, 2021)
Spontaneous dissection of the coronary artery is a well-known entity in young females with myocardial infarction. We report a rare case of spontaneous spiral dissection of the left anterior descending coronary artery (LAD) in a 62-year-old male with history of smoking for 15 years and who has quit smoking 5 years back. Just like an old age saying “footprints are left behind,” the deleterious conundrum of smoking continues even after years together resulting in a spontaneous dissection in the background of damaged arterial elastic media.